2010
DOI: 10.1186/1471-2474-11-168
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of side to side measurements of upper extremity activity levels in healthy subjects

Abstract: BackgroundIn both clinical and occupational settings, ambulatory sensors are becoming common for assessing all day measurements of arm motion. In order for the motion of a healthy, contralateral side to be used as a control for the involved side, the inherent side to side differences in arm usage must be minimal. The goal of the present study was to determine the reliability of side to side measurements of upper extremity activity levels in healthy subjects.MethodsThirty two subjects with no upper extremity pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 50 publications
0
15
0
2
Order By: Relevance
“…The static parameters included the per cent time above a threshold elevation angle (308, 608 and 908; Svendsen et al 2004a) and the 50th, 90th and 99th percentiles of arm elevation (Hansson et al 2010). The dynamic parameters included the 50th, 90th and 99th percentiles of arm velocity (Svendsen et al 2004a), jerk time (Moller et al 2004) and a parameter similar to activity counts (Acuna et al 2010). Arm velocity was calculated by differentiating the elevation angle data set using the central difference method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The static parameters included the per cent time above a threshold elevation angle (308, 608 and 908; Svendsen et al 2004a) and the 50th, 90th and 99th percentiles of arm elevation (Hansson et al 2010). The dynamic parameters included the 50th, 90th and 99th percentiles of arm velocity (Svendsen et al 2004a), jerk time (Moller et al 2004) and a parameter similar to activity counts (Acuna et al 2010). Arm velocity was calculated by differentiating the elevation angle data set using the central difference method.…”
Section: Discussionmentioning
confidence: 99%
“…The subject was instructed to maintain a seated upright posture while holding a 1-kg weight. Direction was given to perform lateral trunk flexion, which resulted in a perpendicular orientation of the arm to the floor (Hansson et al 2006, Acuna et al 2010. During this alignment procedure, the triaxial accelerometer was connected to a computer so that the acceleration parameters could be observed in real time.…”
Section: Occupationmentioning
confidence: 99%
“…Furthermore, our visual feedback needs longer data processes in order to “make sense” (arm usage); therefore, there is no need for direct visual feedback. Systems to train the upper extremity function with VT feedback in stroke patients have been previously developed (Kapur et al, 2009; Acuna et al, 2010; Bark et al, 2011; Hung et al, 2015). It is known that intensive training after stroke has a positive effect in clinical outcome, but the effect of VT feedback on arm function is unclear (Hung et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The choice of feedback was based on results from studies by de Niet et al [31] and Acuna et al [32]. They showed that in normal persons, the activity levels that are measured with accelerometers are similar for the dominant and nondominant arm during daily life activities, while in stroke survivors the affected arm shows a significantly lower activity level [31].…”
Section: Us"em: Concept Overviewmentioning
confidence: 99%